2016
DOI: 10.1080/1828051x.2016.1194172
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzymes responses of polychaete Perinereis aibuhitensis following chronic exposure to 17β-estradiol

Abstract: The occurrence of 17b-estradiol (E2) in the aquatic environment can lead to damage to the reproductive system, along with other adverse effects including oxidative stress, in aquatic organisms. In the present study, Perinereis aibuhitensis were treated with E2 at 0.1, 1, 10, 100 and 1000 lg/L for 205 d, after which the activities of superoxide dismutase (SOD), catalase (CAT) and glutathione-S-transferase (GST), and the concentrations of glutathione antioxidant biomarker responses were studied. Weight gain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Our results showed a higher GSH level in S1 than in S2, which could be a result of increased synthesis and neutralization of ROS via the thiol group. Dissimilar studies on polychaetes have shown a decrease in GSH level in relation to trace metal accumulation (Lv et al 2016). According to the above results, the significant relationship between antioxidant biomarkers (mainly GSH, SOD and GST) and the concentrations of metals (mainly Cd and Zn) in P. cultrifera tissue suggest the activation of the mechanisms of detoxification due to the generation of ROS.…”
Section: Discussionmentioning
confidence: 62%
“…Our results showed a higher GSH level in S1 than in S2, which could be a result of increased synthesis and neutralization of ROS via the thiol group. Dissimilar studies on polychaetes have shown a decrease in GSH level in relation to trace metal accumulation (Lv et al 2016). According to the above results, the significant relationship between antioxidant biomarkers (mainly GSH, SOD and GST) and the concentrations of metals (mainly Cd and Zn) in P. cultrifera tissue suggest the activation of the mechanisms of detoxification due to the generation of ROS.…”
Section: Discussionmentioning
confidence: 62%
“…Several types of indirect DNA damage are caused by estrogeninduced oxidants, such as oxidized DNA bases, DNA strand breakage, and adduct formation by reactive aldehydes derived from lipid hydroperoxides (Cavlieri et al, 2000). On the other hand, enzymes, such as glutathione, a major endogenous antioxidant, which plays a crucial role in protecting cells from exogenous and endogenous toxins, and which exists in the glutathione reduced (GSH) and glutathione disulphide (GSSG), was reported by Lv et al (2016) an increased dose dependent, specifically the activity of GSSG of P. aibuhitensis exposed to E2; in addition to this, Guti errez-G omez et al (2016) also found a significant increase in the activity of the antioxidant enzymes superoxide dismutase, the first defense and the main enzyme responsible for the conversion of superoxide anion to hydrogen peroxide, and glutathione peroxidase in blood of C. carpio exposed to concentration of 1 mg L À1 E2 at 96 h; the increase of these enzymes could explain the results in the comet assay that demonstrated less damage to concentration of 1 mg L À1 , evidencing a greater activity as a mechanism to counteract oxidative DNA damage induced by E2. However, occasionally, such damage is not effectively repaired or is erroneously repaired, eliciting changes in the original DNA sequence (Cavalieri and Rogan, 2014), for this reason, and to evidence the damage, the comet assay is often applied in conjunction with the MNi test, that due to its simplicity, is one of the most applicable techniques to identify genomic alterations in environmental animals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of aquatic wildlife that are directly exposed to contaminants, often provide early indications of potential environmental problems. A few studies report E2 can produce different harmful effects, for example, is an endocrine disrupter at concentrations above 200 ng L À1 in O. mykiss (Marlatt et al, 2006), affect the reproduction of O. javanicus at concentrations greater than 16 ng L À1 (Imai et al, 2005), can decrease the capacity of cellular antioxidant systems in P. aibuhitensis at concentrations greater than 0.1 mg L À1 (Lv et al, 2016) and can induce immunomodulatory changes and neurotoxicity in different organisms (Thilagam et al, 2014). On the other hand, in vitro assays have shown that at low concentrations (1e10 ng L À1 ) of E2 induce feminization in some species of male wild fishes (Routledge et al, 1998), and changes the hepatic gene expression of the vitellogenins and choriogenins in P. flesus (Williams et al, 2007).…”
Section: Introductionmentioning
confidence: 99%